Radiological tests versus pathological diagnostics: Complimentary or antagonistic relationship? The experience of a tertiary hospital - Maria A Arafah; Hala M Kfoury (Wolters Kluwer Medknow Publications, 2017)
Introduction: Early detection of breast cancer plays a pivotal role in the outcome of the disease. Diagnostic modalities encompass radiological and pathological findings. The aim of this study is to evaluate the correlation between the results of these two modalities in a tertiary hospital. Materials and Methods: From a total of 180 patients, 203 ultrasound-guided breast core needle biopsies (US-CNBs) were included in this study over a period of a year (May 2015 - May 2016). All clinical parameters, the site of the biopsy, the size of the needle, the radiological findings, the pathological diagnoses as well as all available follow-up data were reviewed. The concordance between the radiological and pathological results was studied and a statistical analysis conforms to the Pearson Chi-square test was applied. Results: The majority of our patients were above 40 years of age. A strong and statistically significant association was noted between radiological findings and histopathological results (Pearson's Chi-square test = 186.28, P ≤ 0.0001) with only four discordant cases (1.97%). This discrepancy was not statistically associated with age, site of biopsy, needle size, or number of cores obtained (P = 0.621, P = 0.584, P = 0.786, and P = 0.478, respectively). Conclusions: US-CNB is an accurate method in the diagnosis of breast lesions. Radiological and pathological correlation is of utmost importance in relation to patient's care and to reduce false rates. Follow-up of concordant benign lesions is essential. In addition, the importance of a multidisciplinary breast conference during which input from all teams caring for the patient is strongly emphasized.